2019
DOI: 10.1097/prs.0000000000005665
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Use of Intravenous Unfractionated Heparin after Digital Replantation: A Randomized Controlled Trial Involving Three Groups

Abstract: Background: The purpose of this study was to clarify the appropriate use of unfractionated heparin as an anticoagulation agent after digital replantation. Methods: This study was a prospective, randomized, single-blind, blinded-endpoint method, three-arm, parallel-group, controlled clinical trial conducted at a single institution. A total of 88 patients (101 fingers) following digital amputation and subsequent repair by anastomosis of both arteries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…However, Zhu et al 16 demonstrated no significant difference in digital survival among patients who received LMWH 4000 units compared with untreated controls (91% versus 89%, respectively; P > 0.05). Similarly, Nishijima et al 18 found no significant difference in digital survival among patients treated with 10,000 units intravenous heparin, 17,500 units intravenous heparin, and untreated controls (79% versus 89% versus 84%, respectively; P > 0.05). These findings are further supported by Veravuthipakorn and Veravuthipakorn, 21 who report a 91% digital survival rate without the routine use of perioperative thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, Zhu et al 16 demonstrated no significant difference in digital survival among patients who received LMWH 4000 units compared with untreated controls (91% versus 89%, respectively; P > 0.05). Similarly, Nishijima et al 18 found no significant difference in digital survival among patients treated with 10,000 units intravenous heparin, 17,500 units intravenous heparin, and untreated controls (79% versus 89% versus 84%, respectively; P > 0.05). These findings are further supported by Veravuthipakorn and Veravuthipakorn, 21 who report a 91% digital survival rate without the routine use of perioperative thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 90%
“…Lee et al 9 report that patients who received a continuous heparin infusion (target aPTT 51–70 seconds) had a significantly higher incidence of blood transfusion compared with patients who received 12,500 units intravenous bolus heparin. Nishijima et al 18 reported a significantly higher incidence of venous congestion in patients who received postoperative heparin (either 10,000 units or 17,500 units) versus controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations